Revisiting some important heritage bridges of Calcutta, India. Issue 1 (19th February 2020) - Das, Anirudha; Roy, Partha
Abstract : This paper attempts to cover the planning, design and construction of five bridges in Calcutta, India, reconstructed after World War I and still in operation, constructed across the city's Circular Canal and Tolly Nullah. These bridges were reconstructed with an aim to replace the existing bridges at these locations, which were unsuitable due to the emerging city traffic conditions. All these bridges are still in operation (except Chitpore Bridge, which is currently under inspection for retrofitting). The five bridges covered are the twin-leaf bascule bridge at Kidderpore, Tollygunge Bridge crossing Tolly Nullah, Beliaghata Bridge across the Circular Canal, Alipore Bridge across Tolly Nullah at Alipore and Chitpore Bridge over the Circular Canal. The first one is a twin-leaf rolling lift bascule structure with counterweights disposed below the roadway level. The bridges at Tollygunge, Alipore and Chitpore are of reinforced-concrete bowstring type. Beliaghata Bridge is a reinforced-concrete three-hinged arch-type bridge. These bridges were mostly supported on piled foundations with innovative solutions adopted to tackle the poor-quality alluvial Calcutta soil at these sites. Advanced construction techniques were adopted considering the type of traffic, existing utilities and available space at construction sites. This paper converges to their present condition and tries to identify possible rehabilitation methods.